Assessing the Role of Operative Intervention in Elderly Patients With Nonfunctional Pancreatic Neuroendocrine Neoplasms. Issue 4 (11th April 2022) - Hue, Jonathan J.; Sugumar, Kavin; Mohamed, Amr; Selfridge, J. Eva; Bajor, David; Hardacre, Jeffrey M.; Ammori, John B.; Rothermel, Luke D.; Winter, Jordan M.; Ocuin, Lee M.
Abstract : Objectives: Resection of locoregional pancreatic neuroendocrine neoplasms (PanNENs) is typically recommended, but there is a paucity of data on the management of elderly patients. Methods: The National Cancer Database (2004–2016) was queried for patients 80 years or older with localized PanNENs. Patients were grouped as nonoperative or operative management. Postoperative outcomes and survival were compared. Results: In total, 591 patients were included: 202 underwent resection, and 389 did not. Increasing age and pancreatic head tumors were associated with lower likelihood of resection. The overall 90-day mortality rate was 6.4%, which was higher for pancreatoduodenectomy than distal pancreatectomy (13.6% vs 5.1%, respectively). Operatively managed patients had longer median survival (80.8 vs 45.0 months, P < 0.001), and this association was independent of tumor location. On multivariable Cox regression, resection remained associated with longer survival (hazard ratio, 0.69; 95% confidence interval, 0.50–0.95). Among operatively managed patients, age and tumor location were not associated with survival; however, greater comorbidity and high-risk tumor-specific features were associated with worse survival. Conclusions: Resection of nonfunctional PanNENs in elderly patients is associated with improved survival compared with nonoperative management. Resection could be considered in appropriate operative candidates, regardless of tumor location, but the perioperative mortality rate must be considered.